Total quality management : key concepts and case studies / D. R. Kiran - Kiran, D. R.
The book provides the full range of management principles and practices that govern the quality function, covers the fundamentals and background needed, as well as industry case studies and comprehensive topic coverage, making it an invaluable reference to both the novice and the more experienced individual.